(untitled) (Journal of the College of Basic Education, 2022)
When a conversation takes place between students of literature and its critics regarding theoretical criticism and its Hazem Al-Qartajani is one of his prominent leaders, with whom the discussion revolves, and his bold critical views remain. His correct view of poetry, its origins, and methods of constructing it is admired by all because it attracted the theory Criticism of rhetoricians and critics who preceded him, such as Abu Hilal al-Askari, Abd al-Qaher al-Jurjani, and Ibn Al-Atheer, Al-Alawy, Sahib Al-Taraz, and others, as he digested their theories on the origins of literary creativity in the fields of poetry and prose, but he did not stop at the limits of following, and in the field of apprenticeship, but was able with his mind The feat is to benefit from the represented Greek criticism